Relations of Latin American Pedagogy and Liberation Pedagogy. Epistemological Study Based on Dussel and Freire - Mujica Johnson, Felipe (2024)
In the last decades, new epistemological discussions have been developed to support Latin American pedagogies that distance themselves from the hegemonic discourses of modernity and their colonial accent. In this context, this essay aims to contribute to the understanding of some of the relationships between Enrique Dussel’s pedagogy and Paulo Freire’s pedagogy of liberation. In the first section that contributes to this objective, the three chapters of Dussel’s book La pedagógica latinoamericana and the first two chapters of Freire’s book Pedagogy of the Opressed are presented. From Dussel’s book, the concepts father-State, mother-popular culture, and son-child-people are highlighted as symbols that explain the cultural relations of domination. From Freire’s book, the concepts of oppressors, oppressed, banking education, and liberating education are highlighted. In the second section of the development, a distinction is made on the levels of analysis of each philosopher and some coincidences on the banking dimension, totality, exteriority, otherness, and the hope of a liberated world. To conclude the paper, it is considered that there is a correlation between both philosophers that favor the dialectic of the collective human and the cultural human in Latin American pedagogies.